2005
DOI: 10.1159/000085149
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Body-Focused Behaviors and Social Behaviors as Risk Factors of Eating Disorders

Abstract: Background: The risk factors for adolescent eating disorders are poorly understood. It is generally agreed, however, that interactions with one’s body and interactions with others are two important features in the development of anorexia and bulimia nervosa. Therefore, we assessed a variety of childhood body-focused behaviors and childhood social behaviors in eating-disordered patients as compared to non-eating-disordered subjects. Method: We compared 50 female inpatients with eating disorders (anorexia or bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 102 publications
1
23
0
Order By: Relevance
“…Our study had well-defined AN and BN groups, an older population group and focused on differences in specific feeding/eating problems. Higher rates of childhood feeding problems were also found in inpatients with ED compared to polysubstance dependence individuals and normal controls in a recent study [22]. …”
Section: Discussionmentioning
confidence: 81%
“…Our study had well-defined AN and BN groups, an older population group and focused on differences in specific feeding/eating problems. Higher rates of childhood feeding problems were also found in inpatients with ED compared to polysubstance dependence individuals and normal controls in a recent study [22]. …”
Section: Discussionmentioning
confidence: 81%
“…a Kruskal-Wallis (overall) and Mann-Whitney U-test (pairwise) for continuous variables; Fisher's exact test (overall) and v 2 test (pairwise) for binary variables. b Data on frequency of childhood sexual abuse were previously published [20].…”
Section: Resultsmentioning
confidence: 99%
“…Based on a review of 36 randomized controlled trials, the NHLBI [12] have concluded in their treatment guidelines that behavior therapy has a beneficial effect regarding long-term weight loss in addition to nutrition counseling, physical training, dietary, and pharmacological intervention. Multimodal treatments taking into account the complex biopsychosocial nature of obesity [13] have therefore been recommended by the NHLBI and other guidelines [2, 12]. …”
Section: Introductionmentioning
confidence: 99%